The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jmmp5030093
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Fatigue Response of Aluminum Alloy Friction Stir Welded Joints at Various Post-Processing and Treatments

Abstract: The present study examines the fatigue of friction stir welded (FSW) aluminum 6061, 7075, 1060 joints followed by (i) in situ and sequential rolling (SR) processes, (ii) plastic burnishing (iii) solution-treatment artificial aging (STA), (iv) local alloying through depositing thin copper foils, and (v) inserting alumina powder in the weld nugget zone (NZ). The microstructural features and fatigue life of post-processed joints were compared with those of as-welded joints. The in situ rolling technique offered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…It was observed that copper foil with a thickness of 100 µm resulted in higher tensile strength (101 MPa) than 200 µm thickness (88 MPa). The thicker copper foil caused the excessive formation of the brittle intermetallic compound in the stir zone [167]. The positive effect of TiC nanoparticles on the transverse tensile strength of dissimilar FSW between AA5083-H111 and AA6082-T6 was also suggested [162].…”
Section: Effect Of Reinforcement Particles On the Tensile Strengthmentioning
confidence: 94%
See 3 more Smart Citations
“…It was observed that copper foil with a thickness of 100 µm resulted in higher tensile strength (101 MPa) than 200 µm thickness (88 MPa). The thicker copper foil caused the excessive formation of the brittle intermetallic compound in the stir zone [167]. The positive effect of TiC nanoparticles on the transverse tensile strength of dissimilar FSW between AA5083-H111 and AA6082-T6 was also suggested [162].…”
Section: Effect Of Reinforcement Particles On the Tensile Strengthmentioning
confidence: 94%
“…The additions of various reinforcement particles have been introduced as an improvement strategy for increasing the mechanical properties of FSWed joints of strain-hardened Al alloys. For instance, the effects of TiC [162], TiO 2 [163], and SiC [164] nanoparticles, Cu and pre-mixed Cu-Al Powder [56,165], Al 3 Sc compound [166], and inserting Cu foils [167] on the mechanical properties of FSWed joints of Al alloys have been previously investigated. All of these studies have unanimously reported that the incorporation of reinforcement particles into the gap between two sheets strengthens the stir zone's mechanical properties, provided that appropriate welding parameters are chosen.…”
Section: Incorporation Of Reinforcement Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, several innovative solutions for joining aluminium sheets have emerged in recent decades, i.e., friction stir welding [3,4], self-piercing riveting [5], clinching [6], and orbital/planetary riveting [7]. In particular, orbital riveting is a cold-forming process that gives good results at a lower cost [8].…”
Section: Introductionmentioning
confidence: 99%